Construction and operation of the new Belgian research station, Dronning Maud Land, Antarctica - Pattyn, Frank (2007)
Final Comprehensive Environmental Evaluation Report (CEE). F. Pattyn is one of the principal contributors to this report info:eu-repo/semantics/published